Spironucleus spp. and experimental spironucleosis in salmonids - Guo, Fu Ci (University of Guelph, 2006)
The hexamitid causing systemic infection and mortality in sea-caged ' Oncorhynchus tshawytscha' in Canada is confirmed to be a ' Spironucleus'. It is different from 'Spironucleus barkhanus ' that causes systemic infection in 'Salmo salar' in Norway, and is therefore described as a new species, 'Spironucleus kenti' n. sp. 'Spironucleus kenti' n. sp. is significantly shorter than ' S. barkhanus.' It infects 'O. tshawytscha, Oncorhynchus kisutch, Oncorhynchus mykiss' and 'S. salar', while ' S. barkhanus' only infects 'S. salar. Spironucleus kenti' n. sp. is lysed in fresh plasma ('in vitro') from refractive ' S. salar', while 'S. barkhanus' is lysed in fresh plasma from refractive fishes. 'Spironucleus kenti' n. sp. causes high blood parasitaemia in 'O. tshawytscha', whereas the parasitaemia of 'S. barkhanus' is low in 'S. salar. Spironucleus kenti' n. sp. requires fish plasma supplement for prolonged ' in vitro' culture and it also differs in polypeptide and antigenic profiles from 'S. barkhanus'. Agglutinating antibodies from recovered 'O. tshawytscha' have 16 times higher titres to ' S. kenti' n. sp. than to 'S. barkhanus', while those from recovered 'S. salar' have 32 times higher titres to ' S. barkhanus' than to 'S. kenti' n. sp. Complement fixing antibodies from recovered 'O. tshawytscha' do not fix complement to lyse 'S. barkhanus' and those from recovered ' S. salar' do not cross react with 'S. kenti' n. sp. These differences indicate there are two species of 'Spironucleus' in salmonids. Both 'Spironucleus' spp. can be cultured in Trypticase-Yeast extract-Iron medium without bile supplement. The multiplication of ' S. kenti' n. sp. starts with duplications of the nuclei and cytostomal canals, and is completed with longitudinal division after one set of nuclei has migrated to the opposite end. The mechanism of innate immunity in refractive fishes is lysis of parasite via the alternative complement pathway. Recovered fish are protected, and both humoral and cell mediated immunity are involved in protection. ...